2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--22827
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Educational Benefits of Diversity in Engineering Education: A Multi-Institutional Survey Analysis of Women and Underrepresented Minorities

Abstract: He is now a doctoral candidate in STEM Education with a focus on Engineering Education within the Department of Teaching and Learning at Ohio State. He studies topics including but not limited to cognitive development, learning, teaching, and the social contexts within which they occur. He is an experienced Graduate Teaching Associate with the First-Year Engineering Program. He is also currently the Outreach Chair of the OSU American Society of Engineering Education (ASEE) Student Chapter. His research interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…La confianza fue medida a través de la escala de Tyler y Degoey (1995), comprendida por 9 ítems. La diversidad en el aula de clase fue medida a través del cuestionario de Strayhorn et al (2014), el cual incluye 6 ítems. Los ítems de los tres constructos de medición utilizados fueron evaluados mediante una escala tipo Likert de siete niveles (7 -Siempre, 6 -Casi siempre, 5 -A menudo, 4 -Algunas veces, 3 -Pocas veces, 2 -Casi nunca y 1 -Nunca).…”
Section: Operacionalización De Variablesunclassified
“…La confianza fue medida a través de la escala de Tyler y Degoey (1995), comprendida por 9 ítems. La diversidad en el aula de clase fue medida a través del cuestionario de Strayhorn et al (2014), el cual incluye 6 ítems. Los ítems de los tres constructos de medición utilizados fueron evaluados mediante una escala tipo Likert de siete niveles (7 -Siempre, 6 -Casi siempre, 5 -A menudo, 4 -Algunas veces, 3 -Pocas veces, 2 -Casi nunca y 1 -Nunca).…”
Section: Operacionalización De Variablesunclassified
“…For example, racial diversity can improve educational outcomes such as complex thinking among students in college (Antonio et al, 2004). In STEM fields such as engineering, encouraging contact among undergraduate students from different economic, social, or racial and ethnic backgrounds can produce greater perceived learning gains (Strayhorn, Long, Williams, Dorim e-Williams, & Tillman-Kelly, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Within education, diversity and inclusion (D&I) efforts have been strategized in several ways. First, efforts and interactions focused on D&I have been shown to have positive effects on student learning gains such as "personal/social development, practical competence, and general education" (p. 14) [4]. Other research reported that exposure to D&I during students' first year at college was influential in students' continual engagement in D&I experiences throughout their time at college [5].…”
Section: Introductionmentioning
confidence: 99%